Kepastian Hukum Pendirian Perseroan Perseorangan Tanpa Akta Notariil Berdasarkan Undang-Undang Cipta Kerja - Lubbena, Farhad; Mayasari, I Dewa Ayu Dwi (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The purpose of this study is to examine the legal certainty of an individual company which does not use a notarial deed in its establishment. This study uses a descriptive legal research method. The law approach and legal concept analysis are the approaches used in this research. The collection of legal materials in this journal uses a literature study. The description technique is a method of analyzing legal materials used in this journal referring to the relevant laws and regulations, the collected literature related to the problems of this journal. The results of this study indicate that in the process of establishing a limited liability company there are quite significant differences, namely in Law Number 40 of 2007 with Law Number 11 of 2020 concerning Job Creation. The process of forming a PT generally must be made in the form of a notarial deed. It is different from the process of establishing a sole proprietorship which is regulated in Law Number 11 of 2020 concerning Job Creation, where the establishment process is carried out by completing a statement of establishment which does not have to be written down in the form of a notarial deed. The function of a notarial deed at the establishment of a PT is to protect third parties or the public against misuse of the establishment of a PT and provide a protection for the interests of other PT.